Applying hybrid equal channel angular pressing (HECAP) to pure copper using optimized Exp.-ECAP die - KENTLİ, AYKUT; ÖĞÜT, SERKAN (SPRINGER LONDON LTD, 2021)
Equal channel angular pressing (ECAP), expansion equal channel angular pressing (Exp.-ECAP), and hybrid equal channel angular pressing (HECAP) or (Hybrid ECAP) processes were applied to pure copper specimens within this study. After the application of ECAP, the die used in the application of the Exp.-ECAP process was optimized considering the strain inhomogeneity in the specimen and the maximum load that occurred during the process. Finite element method (FEM), artificial neural network (ANN), and genetic algorithm (GA) were utilized together for the optimization process. The optimized die equally minimizes the pressing load and the strain inhomogeneity that occurred in the specimen. Using the optimized die, Exp.-ECAP and HECAP processes were applied to pure copper. The Exp.-ECAP process was previously applied only for aluminum alloys and magnesium alloys. With the application of the Exp.-ECAP process to pure copper, this gap in the literature was removed. In addition, with the application of the HECAP process, the effects of the Exp.-ECAP passes applied after ECAP were also examined which was not done earlier. The specimens, on which ECAP, Exp.-ECAP, and HECAP processes were applied, were subjected to microstructure analysis and mechanical tests, and the effects of these processes were examined. The results obtained showed that the Exp.-ECAP process gave better results in grain refinement and mechanical properties. The Exp.-ECAP passes applied after the ECAP process within the scope of the HECAP process provided a more homogeneous distribution for the microstructure and the hardness.
Keywords: Pure copper; Mechanical properties; Microstructure; SPD; ECAP; Exp; -ECAP; PLASTIC-DEFORMATION METHOD; MECHANICAL-PROPERTIES; STRAIN INHOMOGENEITY; EXTRUSION; MICROSTRUCTURE; EVOLUTION; PRINCIPLE; BEHAVIOR; HARDNESS; TOOL